The efficacy of Gelam Honey dressing towards excisional wound healing - Tan, Mui Koon; Hasan Adli, Durriyyah Sharifah; Tumiran, Mohd Amzari; Abdulla, Mahmood Ameen; Yusoff, Kamaruddin Mohd (Hindawi, 2012)
Honey is one of the oldest substances used in wound management. Efficacy of Gelam honey in wound healing was evaluated in this paper. Sprague-Dawley rats were randomly divided into four groups of 24 rats each (untreated group, saline group, Intrasite Gel group, and Gelam honey group) with 2 cm by 2 cm full thickness, excisional wound created on neck area. Wounds were dressed topically according to groups. Rats were sacrificed on days 1, 5, 10, and 15 of treatments. Wounds were then processed for macroscopic and histological observations. Gelam-honey-dressed wounds healed earlier (day 13) than untreated and saline treated groups, as did wounds treated with Intrasite Gel. Honey-treated wounds exhibited less scab and only thin scar formations. Histological features demonstrated positive effects of Gelam honey on the wounds. This paper showed that Gelam honey dressing on excisional wound accelerated the process of wound healing.